Utilization of Liveworksheet-Based Interactive Student Worksheets to Increase Student Engagement in Social Studies Learning - Septiana, Khoirun Najmi; Herlina, Meri; Hidayat, Rahmad (SOCIAL PEDAGOGY: Journal of Social Science Education, 2026)
This study aims to enhance student engagement in the social studies learning process by utilising interactive worksheets based on Liveworksheet. This study is motivated by the low level of student engagement in social studies lessons, characterised by a decline in students’ activity, enthusiasm, participation, and critical thinking skills during the teaching and learning process. This study employs a quantitative descriptive research design. Sampling was conducted using the Purposive Sampling technique, resulting in Year 7 being selected as the sample class. Data collection techniques included observation of student engagement during the learning process and documentation. Data analysis utilised quantitative descriptive analysis using average percentages. The results of the study indicate that in the first session, student engagement was in the ‘fair’ category at 76% and improved to the ‘good’ category in the second session, reaching 84%. Students became more active in asking questions, completed tasks on time, and demonstrated higher levels of participation and interest throughout the learning process in the classroom. Consequently, it can be concluded that the use of interactive worksheets based on Liveworksheets is effective in enhancing student engagement in Social Studies lessons.